Validation of the use of firearms for euthanising stranded cetaceans - Hampton, J. O.; Mawson, P. R.; Coughran, D. K.; Vitali, S. D. (J. Cetacean Res. Manage., 2023)
Efforts to euthanise stranded cetaceans remain highly variable in their outcomes, with few field tested operational procedures available. This study sought to validate the efficacy of using modern firearms technology to euthanise small (<6m length) stranded cetaceans. Post-mortem evidence was gathered from the standardised shooting of cetacean cadavers (n = 10), representing six species, using .30 caliber (7.62mm) firearms and blunt solid copper-alloy non-deforming projectiles, in southwestern Australia. The six species studied were Risso’s dolphin, common dolphin, bottlenosed dolphin, pygmy sperm whale, Cuvier’s beaked whale, and humpback whale. Post-mortem data revealed that 100% of bullet wound tracts fully penetrated the skulls of shot animals, with associated indirect skull fracturing, secondary bone missiles and brain parenchyma laceration. The results suggest that appropriate firearms technology is fully capable of inducing instantaneous fatal pathology to the central nervous system of these species. In comparison to alternative methods for the euthanasia of stranded cetaceans, the use of firearms is associated with superior animal welfare outcomes, public safety levels and accessibility. This paper provides a template for the safe, humane and repeatable use of this technique to euthanise <6m length stranded cetaceans.